(untitled) (Bangladesh Journal of Botany, 2025)
In this study; some quality characteristics of menengic (Pistacia terebinthus L.) fruit, which has a high potential to be a functional product in terms of its components, were investigated. For this purpose, moisture, ash, protein, fat, energy, total dietary fiber, total phenolic content, antioxidant activity and color (L*, a*, b*) of menengic fruits were analyzed. The moisture, ash, protein and fat contents of menengic fruit were 5.89, 3.02, 10.08 and 40.27%, respectively. As a result of the analyses, the total dietary fiber content was determined as 4.98%, the total phenolic content was 652.82 mgGAE/100g, antioxidant activity value was 92.38% and the phytic acid content was found to be 4.02 mg/g. The results showed that menengic fruit can be a valuable source for food uses, especially regarding the phytochemical components, protein, fat and fiber. Bangladesh J. Bot. 54(2): 393-396, 2025 (June)